Evaluation of Distance Learning Fiqih Subjects at Madrasah Tsanawiyah in Kudus - Zafi, Ashif Az (Lembaga Pendidikan Hikmatun Najah Blora, 2022)
This research aims to evaluate fiqh learning during the Covid 19 pandemic using the CIPP model at MTsN in Kudus Regency. The research data analysis used is qualitative. This research concludes that the Covid 19 pandemic requires the use of e-learning as a means of learning. E-learning is organized to make learning easier for educators and students during distance learning. This system can be called an effective and efficient system. The characteristics of educators and students are said to be able to master the technology used for learning so that they can support the implementation of e-learning. The availability of adequate facilities and infrastructure, such as laptops and internet networks. For computers/laptops, the Madrasah makes it mandatory for students. The e-learning learning process makes things very easy for educators and students, both in terms of understanding and use. The final results of e-learning during the pandemic decreased but were not significant. The funds needed to implement e-learning are quite large, but this is not a worry for the madrasah because the system is supported by School Operational Assistance. Good interactions occur during e-learning so that fatal obstacles are rarely encountered. Because various stakeholders maximize their interactions so that they can produce learning that has a good impact and effectiveness in e-learning can be created.